Interação e persuasão em artigo de opinião de Carlos Heitor Cony: um enfoque sistêmico-funcional - Silva, Maria Piedade Teodoro da (2013)
The goals of the Portuguese Language teaching for high school, according to the national curriculum Parameters (PCN)-once considered the genres provided for a given cycle, adjusted to your goals and readers-are: understanding the meaning of messages; the development of sensitivity to recognize the implicit and discriminatory contents intentionality or persuasive; and the production of written texts, cohesive and consistent. The first theme chosen for this master's thesis was an examination of the written work of high school students, focusing on the argumentative essay, in order to verify the causes of insufficient notes assigned to them in public and private tenders. It was found, however, that the task required a prior step to this research, the identification of elements that constitute a persuasive argumentative text and well structured. What features would mark a text well evaluated, and who do not support texts judged insufficient? The answer to this question requires a theoretical basis which makes it possible to judge knowingly texts that do not respond satisfactorily to these criteria. The objective of this research is the examination of the persuasion that traverses the opinion piece by Carlos Heitor Cony, published on the website of the Brazilian Academy of letters, skinning! Kill!, by means of theoretical-methodological proposals of Systemic- Functional Grammar. To do so, you must answer the following research questions: (a) how is the gender structure in this article, with a view to the issue of persuasion? (b) how is the relationship between the linguistic forms and the ideology that underlies this articleto ensure the persuasion on the arguments in this text? The results of the analyses show that the generic structure of the article, via interactive, and function of lexical-grammatical choices, through the interactional function, are an option to ensure the persuasion that supports the argument woven by Cony